IMMUNE STATUS OF PATIENTS WITH CHRONIC MICROBIAL ECZEMA AND ELEVATED IGG4 LEVELS TO MOLD ALLERGENS - Popova, I.B.; Kaidashev, I.P.; Yemchenko, Ya.O.; Vasylieva, K.V.; Reznichenko, N.Y.; Kameniev, V.I.; Ishcheikin, K.Ye. (World of Medicine and Biology, 2025)
According to the World Allergy Organization, 40 % of the global population has one or more allergic diseases and daily struggles with the fear of potential asthma attacks, complications, or even death from various allergic reactions. A clear dependence of the development of allergic diseases on the degree of air contamination by fungi and their spores has been established. Therefore, the study of specific immune reactions to antigens of mold and yeast-like fungi is extremely relevant. Overall, elevated levels of specific IgG4 were detected in 95.7 % of patients to at least one of the studied allergens. The frequency of elevated specific IgG4 levels to each of the studied mold allergens was as follows: Mucor racemosus – 65.2 %, Candida albicans – 54.3 %, Aspergillus fumigatus – 41.3 %, Alternaria tenuis – 34.8 %, Penicillium notatum – 6.5 %, Cladosporium herbarum– 4.3 %. For the etiological diagnosis of exacerbations in chronic microbial eczema and uncontrolled disease progression, the determination of specific fungal IgE and IgG is informative. This will clarify the nature of sensitization and enable adequate treatment for patients with chronic microbial eczema.
Keywords: sensitization; mold fungi; microbial eczema; IgG4